Basic Design is Indeed for Expert - Anita Rahardja; D. Rio Adiwijaya (Humaniora, 2011)
This article would argue that basic design in undergraduate design study is equally significant in both freshmen as well as senior years (when projects of simulated professional practice tend to regard contexts as more significant than visual itself). It will be shown that basic design plays a profound role throughout the whole education setting, from lectures, form-creation process, to design criticism and assessments. It even expands its worth into sphere of professional practice, as long as form analysis and form-making ability are still demanded as a vital part of designer’s set of competencies. For how could visual analytic or consideration become less important than e.g. marketing, since designer becomes designer, if and only if he/she has certain competence in visual instead of academic-grade marketing? More after, this brief inquiry employs the method of literary study in conjunction with direct and indirect observation through the internet concerning design education and its practice, followed by critical reflections. The outcome of this study would be a firm recommendation for basic design engagement through the whole education years, since its descriptive-generative functions of visual are yet highly relevant, for they lie at the very core of visual communication design discipline itself.